2019
DOI: 10.1093/gji/ggz517
|View full text |Cite
|
Sign up to set email alerts
|

Joint estimation of gravity anomalies using second and third order potential derivatives

Abstract: Satellite gradiometry data provide the framework for estimating and validating Earth's gravity field from second and third order derivatives of the Earth's gravitational potential. Such procedures are especially useful when applied locally, as they relate to local and regional characteristics of the real gravity field. In the present study a joint inversion procedure is proposed for the estimation of gravity anomalies at sea surface level from second and third order potential derivatives, based on a standard G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The essence of Gauss‐Markov estimation is a special case of weighted least square estimation 59 . Its function is to make the error variance of fusion result smaller than that of single model prediction result.…”
Section: Multiple Models Fusion Based On Gauss‐markov Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The essence of Gauss‐Markov estimation is a special case of weighted least square estimation 59 . Its function is to make the error variance of fusion result smaller than that of single model prediction result.…”
Section: Multiple Models Fusion Based On Gauss‐markov Estimationmentioning
confidence: 99%
“…The essence of Gauss-Markov estimation is a special case of weighted least square estimation. 59 Its function is to make the error variance of fusion result smaller than that of single model prediction result. The Gauss-Markov estimation algorithm is as the following: Supposing there are L prediction models.…”
Section: Multiple Models Fusion Based On Gauss-markov Estimationmentioning
confidence: 99%
“…With the first measurement of radial gravitational curvatures (or gravity curvatures, GC, third-order derivatives of the gravitational potential) using the atom interferometry sensors in the laboratory condition (Rosi et al 2015), the subsequent study of the GC was focused on their theory and simulation applications in geodesy and geophysics (Šprlák and Novák 2015(Šprlák and Novák , 2017Hamáčková et al 2016;Sharifi et al 2017;Novák et al 2017;Pitoňák et al 2017Pitoňák et al , 2018Pitoňák et al , 2020Shen 2018a, b, 2019;Novák et al 2019;Du and Qiu 2019;Romeshkani et al 2020Romeshkani et al , 2021. The GC were more sensitive to field sources than the loworder gravitational effects (i.e., GP, GV, and GGT) (Heck 1984;Du and Qiu 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The GC were more sensitive to field sources than the loworder gravitational effects (i.e., GP, GV, and GGT) (Heck 1984;Du and Qiu 2019). Numerical results showed that they were more sensitive to local characteristics of the gravity field (Romeshkani et al 2020), can better describe areas with large terrain undulations and the junction of the land and sea (Deng and Shen 2019), and can more accurately identify the near-underground shallow density structure in the spatial domain (e.g., caves, salt domes, sediment base morphology, continental margins, and hidden fault systems) (Novák et al 2019) than the low-order gravitational effects. These advantages of the GC are important for studying the distribution of materials and geological structures within the Earth.…”
Section: Introductionmentioning
confidence: 99%